2020
DOI: 10.3389/fimmu.2020.02031
|View full text |Cite
|
Sign up to set email alerts
|

TLT2 Suppresses Th1 Response by Promoting IL-6 Production in Monocyte Through JAK/STAT3 Signal Pathway in Tuberculosis

Abstract: The function of triggering receptor expressed on myeloid cell-like transcript 2 (TLT2) has not been characterized and their role in pulmonary tuberculosis (TB) remains unclear. In this study, we found that surface TLT2 was up-regulated in human monocytes of patients with active TB compared to healthy subjects. In vitro, TLT2 expression was induced in human monocyte cell line THP-1 cells after bacillus Calmette-Guérin (BCG) or Mycobacterium tuberculosis (Mtb) H37Rv infection. Knockdown of TLT2 by siRNA transfec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…injection of H37Rv show organized granulomas containing T cells and macrophages that resembled lesions observed in human TB (31). In our study, H&E staining showed pathologic changes characterized by lung destruction, granuloma formation, and immune cell infiltrates, as reported by previous studies and by others and us (32,33). Although TARM-1 enhanced the activation of macrophage and Th1 differentiation in vivo, TARM-1 blockade aggravated lung pathology in mice after H37Rv infection and increased bacterial load.…”
Section: Discussionsupporting
confidence: 89%
“…injection of H37Rv show organized granulomas containing T cells and macrophages that resembled lesions observed in human TB (31). In our study, H&E staining showed pathologic changes characterized by lung destruction, granuloma formation, and immune cell infiltrates, as reported by previous studies and by others and us (32,33). Although TARM-1 enhanced the activation of macrophage and Th1 differentiation in vivo, TARM-1 blockade aggravated lung pathology in mice after H37Rv infection and increased bacterial load.…”
Section: Discussionsupporting
confidence: 89%
“…STAT3 plays a key role in activating NKT cells by targeting its downstream MHC class I-related chain (MIC) [ 22 ]. The activation of STAT3 may suppresses Th1 response during tuberculosis infection [ 23 ]. TIRC7 inhibits Th1 cells by upregulating the expression of CTLA‑4 and STAT3 in mice with acute graft‑versus‑host disease [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using proteomics analysis and TLT-2 knockdown, Xu and colleagues revealed that TLT-2 activates NF-κB signaling by inhibiting IκBα to promote the expression of granzyme B (GZMB) and enhance the immune function and proliferation ability of CD8 + T cells [ 29 ]. However, in contrast to its overall proinflammatory effect on other cell types, TLT-2 expressed in monocytes promotes interleukin-6 (IL-6) expression via the Janus kinase (JAK)/signal transducer and activator of transcription 3 (STAT3) pathway, blocks Th1 differentiation and hinders the immune response to tuberculosis [ 30 ]. These studies suggest that TLT-2 is an important modulator of both the innate and adaptive immune systems.…”
Section: Receptor Of B7-h3mentioning
confidence: 99%